2018
DOI: 10.3390/nu10091141
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin-3-gallate and 6-OH-11-O-Hydroxyphenanthrene Limit BE(2)-C Neuroblastoma Cell Growth and Neurosphere Formation In Vitro

Abstract: We conducted an in vitro study combining a rexinoid, 6-OH-11-O-hydroxyphenanthrene (IIF), and epigallocatechin-3-gallate (EGCG), which is the main catechin of green tea, on BE(2)-C, a neuroblastoma cell line representative of the high-risk group of patients. Neuroblastoma is the most common malignancy of childhood: high-risk patients, having N-MYC over-expression, undergo aggressive therapy and show high mortality or an increased risk of secondary malignancies. Retinoids are used in neuroblastoma therapy with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 37 publications
(50 reference statements)
0
4
0
Order By: Relevance
“…Farabegoli et al, discovered that the combinational treatment of EGCG and a rexinoid, 6-OH-11-O-hydroxyphenanthrene [IIF] inhibits neuroblastoma cell growth and neurosphere formation in vitro [8]; the authors concluded that the association of EGCG to IIF might be able to overcome the incomplete success of retinoid treatments in neuroblastoma patient without toxic effects.…”
mentioning
confidence: 99%
“…Farabegoli et al, discovered that the combinational treatment of EGCG and a rexinoid, 6-OH-11-O-hydroxyphenanthrene [IIF] inhibits neuroblastoma cell growth and neurosphere formation in vitro [8]; the authors concluded that the association of EGCG to IIF might be able to overcome the incomplete success of retinoid treatments in neuroblastoma patient without toxic effects.…”
mentioning
confidence: 99%
“…EGCG is a biological polyphenol commonly detected in green tea [ 525 ]. Numerous studies have investigated the anti-cancer potential of EGCG and its benefits, such as reversal of drug resistance and inhibition of cancer stem cells [ 525 ]. Proteomics analysis demonstrated that the DEAD-box RNA helicase, p68, is a binding target of EGCG [ 526 ].…”
Section: Myc Modulators As Cancer Treatmentsmentioning
confidence: 99%
“…Farabegoli et al [191] Drugs (combinations) tested, targeted molecular drivers and the studies are listed. A complete list if CSC-targeting compounds, mode of action in and beyond NB is discussed in detail elsewhere [188] specific candidate in all NB-CSCs within the tumor and (2) the presence of candidate marker(s) in normal non-tumorigenic stem cells highly limit their use in developing a CSC-targeted approach.…”
Section: Tnks Cd133mentioning
confidence: 99%